The comments of voices on the appearance of patients with psychosis: 'the voices tell me that I am ugly'. Issue 5 (September 2019) - Waite, Felicity; Diamond, Rowan; Collett, Nicola; Chadwick, Eleanor; Bold, Emily; Teale, Ashley-Louise; Taylor, Kathryn M.; Kirkham, Miriam; Twivy, Eve; Causier, Chiara; Carr, Lydia; Bird, Jessica C.; et al.
Abstract : Background: There are high rates of obesity and low self-esteem in patients with psychosis. The occurrence of negative voice content directly about appearance is therefore plausible. Derogatory comments about appearance are likely to be distressing, increase depression and contribute to social withdrawal. Aims: To systematically assess the occurrence of voice content regarding appearance and identify correlates. Method: Sixty patients experiencing verbal auditory hallucinations at least once a week in the context of non-affective psychosis completed a measure assessing positive and negative voice content about appearance. They also completed assessments about body image, self-esteem, psychiatric symptoms and well-being. Results: Fifty-five (91.7%) participants reported hearing voices comment on their appearance. A total of 54 (90%) patients reported negative voice content about their appearance with 30 (50%) patients experienced negative appearance comments on a daily basis. The most common negative comment was 'the voices tell me that I am ugly' ( n = 48, 80%). There were 39 (65%) patients who reported positive voice content on appearance. The most frequent positive comment was 'I look as nice as other people' ( n = 26, 43.3%). Negative voice content about appearance was associated with body image concerns, paranoia, voice hearing severity, depression, worry, negative self-beliefs and safety-seeking behaviours. Positive appearance voice content was associated with greater body esteem and well-being and lower levels of depression and insomnia. Conclusions: Voice content about appearance is very common for patients seen in clinical services. Negative voice content may reflect – and subsequently reinforce – negative beliefs about one's appearance, low self-esteem, worry and paranoia. Declaration of interest: None.